Long-term ecological and evolutionary dynamics in the gut microbiomes of carbapenemase-producing Enterobacteriaceae colonized subjects - Kang, Jonathan T. L.; Teo, Jonathan J. Y.; Bertrand, Denis; Ng, Amanda; Ravikrishnan, Aarthi; Yong, Melvin; Ng, Oon Tek; Marimuthu, Kalisvar; Chen, Swaine L.; Chng, Kern Rei; Gan, Yunn-Hwen; Nagarajan, Niranjan (Nature microbiology, 2022)
Long-term colonization of the gut microbiome by carbapenemase-producing Enterobacteriaceae (CPE) is a growing area of public health concern as it can lead to community transmission and rapid increase in cases of life-threatening CPE infections. Here, leveraging the observation that many subjects are decolonized without interventions within a year, we used longitudinal shotgun metagenomics (up to 12 timepoints) for detailed characterization of ecological and evolutionary dynamics in the gut microbiome of a cohort of CPE-colonized subjects and family members ( n = 46; 361 samples). Subjects who underwent decolonization exhibited a distinct ecological shift marked by recovery of microbial diversity, key commensals and anti-inflammatory pathways. In addition, colonization was marked by elevated but unstable Enterobacteriaceae abundances, which exhibited distinct strain-level dynamics for different species ( Escherichia coli and Klebsiella pneumoniae ). Finally, comparative analysis with whole-genome sequencing data from CPE isolates ( n = 159) helped identify substrain variation in key functional genes and the presence of highly similar E. coli and K. pneumoniae strains with variable resistance profiles and plasmid sharing. These results provide an enhanced view into how colonization by multi-drug-resistant bacteria associates with altered gut ecology and can enable transfer of resistance genes, even in the absence of overt infection and antibiotic usage. Longitudinal shotgun metagenomics reveal changes in the gut microbial ecology upon carbapenemase-producing Enterobacteriaceae colonization and decolonization of adult subjects.